REHABILITATION IN DISEASES OF THE LUMBAR SPINE AND OSTEOCHONDROSIS - Israilova Sokhiba Buribayevna; Мелибайева Умида Мирзабайевна (Web of Journals Publishing, 2024)
This article explores the significance of rehabilitation in managing diseases of the lumbar spine, with a focus on osteochondrosis. The study delves into the effectiveness of various rehabilitation methods, encompassing exercise therapy, physiotherapy, and interventional strategies. Through a comprehensive literature analysis, the article aims to provide insights into the current state of rehabilitation practices and their impact on patients with lumbar spine disorders. The methodology involves reviewing relevant studies and clinical trials to extract valuable information regarding the outcomes of rehabilitation interventions. The results section will present key findings, followed by a discussion of their implications. The conclusion will summarize the importance of rehabilitation in treating lumbar spine diseases, offering suggestions for future research and clinical applications.
Keywords: Lumbar spine, osteochondrosis, rehabilitation, exercise therapy, physiotherapy, chronic back pain, interventional strategies.